2006
DOI: 10.1177/0022427805280068
|View full text |Cite
|
Sign up to set email alerts
|

Official Labeling, Criminal Embeddedness, and Subsequent Delinquency

Abstract: This article examines the short-term impact of formal criminal labeling on involvement in deviant social networks and increased likelihood of subsequent delinquency. According to labeling theory, formal criminal intervention should affect the individual's immediate social networks. In many cases, the stigma of the criminal status may increase the probability that the individual becomes involved in deviant social groups. The formal label may thus ultimately increase involvement in subsequent deviance. We use pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
268
2
10

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(291 citation statements)
references
References 58 publications
(83 reference statements)
11
268
2
10
Order By: Relevance
“…This is problematic when sanctions are used to induce behavioral change in people who are showing the undesired behavior. Indeed, literature on reintegrative shaming suggests that sanctions work counterproductive because they express rejection of the person (Braithwaite 1989(Braithwaite , 2006 and other findings in criminology demonstrate that actually having received a punishment (rather than only the threat of it) evokes criminal behavior (Bernburg et al 2006;Paternoster and Piquero 1996). A recent illustration of this is a study performed by Harris and Worden (2014) among police officers who had obtained a complaint.…”
Section: Discussionmentioning
confidence: 99%
“…This is problematic when sanctions are used to induce behavioral change in people who are showing the undesired behavior. Indeed, literature on reintegrative shaming suggests that sanctions work counterproductive because they express rejection of the person (Braithwaite 1989(Braithwaite , 2006 and other findings in criminology demonstrate that actually having received a punishment (rather than only the threat of it) evokes criminal behavior (Bernburg et al 2006;Paternoster and Piquero 1996). A recent illustration of this is a study performed by Harris and Worden (2014) among police officers who had obtained a complaint.…”
Section: Discussionmentioning
confidence: 99%
“…In criminology, labeling theory predicts that justice intervention puts a deviant label on an offender which causes him or her to become more deeply imbedded in a deviant social group (Becker, 1963;Lemert, 1967). In line with this, recent research has shown that having received punishment evokes criminal behavior (Paternoster & Piquero, 1996;Bernburg, Krohn, & Rivera, 2006). Also, literature on reintegrative shaming underlines that sanctions work counterproductive as they communicate rejection of the person (J.…”
Section: Moral Judgments and Behaviormentioning
confidence: 86%
“…Secondly, most legal cases are not reported or published in legal databases. It is important to note that this distinction does not refer to whether the case is available to the public, but whether the decision is published and circulated for commercial purposes (Arnold, 1999). Furthermore, when the court believes that a particular case does not have precedential value or does not add substantively to the relevant body of law, the court can reserve the case as unpublished (in the United States) or unreported (in Canada).…”
Section: Methodsmentioning
confidence: 99%